Бренд-менеджмент як один зі способів підтримки стабільного фінансового розвитку бізнесу - Мороз, М. Ю. (ХНУРЕ, 2024)
This work explores the fundamental role of brand management in driving sustainable financial development within businesses. By shaping consumer perceptions and fostering loyalty, effective brand management establishes a foundation for long-term success. It highlights the significant impact of brand equity on revenue growth, profitability, and market share. Ultimately, the findings underscore the strategic imperative for businesses to prioritize brand management as a key driver for enduring financial stability and growth in today's competitive marketplace.
Keywords: бренд-менеджмент; фінансовий розвиток бізнесу